THINKING INTERACTION OF STUDENT IN SOLVING OPEN-ENDED PROBLEMS - Syarifudin, Syarifudin; Purwanto, Purwanto; Irawan, Edy Bambang; Sulandra, I Made; As'ari, Abdur Rahman; Subanji, Subanji (International Journal of Insights for Mathematics Teaching (IJOIMT), 2018)
The purpose of this research is to describe the process of thinking interaction of students in solving the open-ended problem. The thinking interaction of students' in this study is defined as an activity of exchanging thoughts between students one with other students through communication to produce the suitability of the thinking process between them through the resolution of open-ended problems. This study was conducted on a group of junior high school students with heterogeneous capabilities, consisting of 5 students, and have taken the material to build space. The data of thought interaction activity is obtained from discussion result in solving open-ended problem analyzed by information processing theory. Students' thinking interaction activities begin from one subject person who gives statement and understanding about the problem provided. Activity mutual ideas, complement or give feedback to other subject's comments, ask questions that have not been understood, or give an explanation in deciding the answer to be agreed. Subsequent activities decide the answer orally to be written by each subject. All subjects poured the agreed result on the answer sheet, but there were still doubts from the two subjects on the answer, so the subject looked back at the answers from other subjects. Some subjects continue to write answers and in the end, each subject has a form of answer in accordance with their respective understanding.